MODEL PENGELOLAAN TEACHING FACTORY SEKOLAH MENENGAH KEJURUAN - Wijaya, M Burhan R (Universitas Negeri Semarang, 2013)
This study aims to identify and develop management models Factory Teaching Vocational School through a series of tests and validation of the model with the approach of reasearch and Development. Teaching Factory Management Models at Vocational Schools is a concept that combines learning management approach learning Competency Based Training (CBT) and Production Based Training (PBT) in the real atmosphere so that the process of achieving competence or skill skills life skills (life skills) in accordance with the standards of graduate work in the industrial world. In particular, this study aims to formulate design management model development Teaching Factory Vocational School. To achieve the research objectives above using the approach of Research and Development, through preliminary studies, design development models, testing and validation. Preliminary study phase is planned to take the flow / stage as follows: the study of literature, study / collection of field data, and a description and analysis of field findings (factual), namely: (1) the description of the characteristics of vocational school with a standard performance indicators that can be poured as the content of the development of Teaching Factory, (2) description of the characteristics and potential development group management model Tefa as an outcome groups to develop and implement management models Tefa for Vocational Schools (3) description of the characteristics of potential stakeholders to support the development and implementation TEFA management model, and (4) preparation of the management model TEFA for Vocational Schools excellence and innovative. Trial design done on a limited scale model group. Then the model was accompanied by outcome group to develop and implement a model TEFA for Vocational Schools to determine whether the model developed can be applied correctly. Data analysis in this study, the preliminary study stage, the findings or the facts about productive learning programs implemented are described in the form of data presentation, and then analyzed (interpreted) qualitative. The process and results of design development done in a peer-group analysis and expert judgment. And the results of trials presented in the form of data as well as design (applicability) were analyzed by descriptive qualitative. Teaching Factory management model developed can be applied in the management of Teaching Factory for Vocational School and serves as a guide for managers Teaching Factory (principals, teachers, industry partners) and can produce a constructive contribution in a partnership between Vocational Schools with industry.